Potensi Perdagangan Komoditas Lada dari Indonesia ke Vietnam sebagai Salah Satu Pasar Non-Tradisional: Institut Pertanian Bogor - Fathya Dhiya Ulhaq Fathya; Ana Himatul Wahidah; Usi Uswatun Hasanah; Melisa Indri Hartanti; Arifah Fajrina (IPB University, 2021)
The trend of slowing export demand from Indonesia's main export destination countries currently requires Indonesia to diversify its exports to other countries. Vietnam is a country that has the potential as a destination for export diversification. The most potential product to be utilized in this export diversification is pepper. This study aims to analyze the potential and competitiveness of pepper exports in the Vietnamese market; as well as analyze tariff and non-tariff barriers to pepper exports to the Vietnamese market. The data used in this study are time series data for 2010-2019 sourced from the United Nations of Commodity Trade Database (UN-Comtrade) and the World Integrated Trade Solution (WITS). The analysis will be carried out through the analysis of ISP, IIT, RCA, EPD, as well as FI and CR. As for the results of this study, trade integration between Indonesia and Vietnam is still very weak (IIT), the competitiveness of Indonesia's pepper commodity is still low when compared to other countries in the Vietnam market (EPD), and Indonesia's pepper exports to Vietnam are affected by Non- Tariff Measure/NTM (FI and CR). Although, the Indonesian pepper commodity in the Vietnamese market is the most superior commodity (ISP), has great potential (RCA), and has a fairly high competitiveness (X-Model). Therefore, the recommended policy of the government is to increase world trade cooperation; internal improvements through the establishment of pepper farmer institutions, product diversification, and improving pepper quality; as well as pay attention to the supervision of aspects of Quality Control of pepper.